The disposition effect and admiration seeking - Suchanek Max; Minh-Lý Liêu (Review of Financial Economics, 2021)
This paper examines the relationship between the disposition effect and personality traits and aims to find an additional explanation of this bias in a willingness to pay for admiration. We conduct a personality assessment, a stock trading game and a sealed-bid English auction for 84 individual investors. The gathered data correspond with the literature on a descriptive level; however, even though admiration-seeking behavior is an important part of social interaction, there is no significant willingness to pay for it. Furthermore, we do not see any influence of personality on the disposition effect. Our findings add to the ongoing discussion of personality traits in connection with behavioral biases.
Keywords: 330; admiration; big five; dark triad; disposition effect; personality traits